Endogenous Lobbying - Leonardo Felli; Antonio M. Merlo (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we endogenize the number and characteristics of lobbies in a citizen-candidate model of representative democracy where citizens can lobby an elected policy-maker. We find that lobbying always matters. That is, lobbying always affects equilibrium policy outcomes. Moreover, only one policy outcome emerges in equilibrium. An extremist candidate is elected and implements a centrist policy that differs from the one most preferred by the median voter. These results are in contrast with the ones obtained in the context of a citizen-candidate model where lobbies are exogenous.
Keywords: 330; Lobbying; citizen-candidate; representative democracy; electoral competition